The differential effects of oil demand and supply shocks on the global economy - Cashin, Paul (IMF working paper, 2012)
We employ a set of sign restrictions on the generalized impulse responses of a Global VAR model, estimated for 38 countries/regions over the period 1979Q2-2011Q2, to discriminate between supply-driven and demand-driven oil-price shocks and to study the time profile of their macroeconomic effects for different countries. The results indicate that the economic consequences of a supply-driven oil-price shock are very different from those of an oil-demand shock driven by global economic activity, and vary for oil-importing countries compared to energy exporters. While oil importers typically face a long-lived fall in economic activity in response to a supply-driven surge in oil prices, the impact is positive for energy-exporting countries that possess large proven oil/gas reserves. However, in response to an oil-demand disturbance, almost all countries in our sample experience long-run inflationary pressures and a short-run increase in real output.